Development of Interactive STEAM Storybook to Improve Critical Thinking In 3rd Grade - Putri Aryanti, Virli Dian; Airlanda, Gamaliel Septian (Universitas Majalengka, 2024)
The research aims of this study are to develop the storybook STEAM-based learning (Science, Technology, Engineering, Arts, Mathematics) for mathematic learning to improve critical thinking skills in grade 3 students in Elementary Public School Bringin 02. This media was developed based on the STEAM approach, so the use of media through the syntax of analyzing, synthesizing, making conclusions, and organizing strategies and tactics. The excellence of this innovative work focuses on improving critical thinking skills and scientific literacy skills. The excellence of this innovative work focuses on improving critical thinking skills. The type of research is Research and Development (R&D) using the Borg and Gall development model. The STEAM Activity: The Three Sides of My Family learning media is deemed suitable by three experts, including a children's literature expert with a 91% rating in the excellent category, a media expert with a 96% rating in the excellent category, and a content expert with an 82% rating in the excellent category. The STEAM Activity book is considered practical by students at Public School Bringin 02, receiving a 100% rating in the excellent category. Using an independent samples t-test, the effectiveness is found to be significant at 0.013, indicating that the STEAM Activity book is effectively used to enhance students' critical thinking skills.